Obstacles of Patient Safety Culture Implementation to Prevent and Control of Healthcare-Associated Infections (Hais) During Covid-19 Pandemic: A Phenomenological Study - Bayu herlambang Bayu; Pamungkas Rian Adi; Anastina Tahjoo (Alta Dharma Publisher, 2021)
Background: The implementation of patient safety is an effective strategy in preventing and managing Healthcare-Associated Infections (HAIs). Objective: This study aimed to explore the obstacles in implementing the patient safety culture by dental co-assistant (co-ass) on prevention and control of HAIs in the covid-19 pandemic. Method: This study used a qualitative method with a phenomenological study approach. The sample in this study was 16 key informants consisting of 10 dental co-assistant, five dental nurses, and one hospital director. The sampling technique used the purposive sampling technique. Results: The results of this study indicate that there were five obstacles in implementing the patient safety culture to prevent and control HAIs, including 1) the rules were not strict in the implementation of patient safety culture; 2) poor attitude by the dental co-assistant (co-ass); 3) the facilities are not feasible to support the implementation of patient safety culture; 4) inadequate patient safety culture guidelines, and 5) lack of supervision in the implementation of patient safety culture. Conclusion: The results of this study provide important information related to obstacles faced by dental co-assistant in the implementation of patient safety culture to prevent and control HAIs during the covid 19 pandemic. The dental co-assistant should focus on the implementation of patient safety culture to suppress the occurrence of HAIs.